Iraq Ablaze - "Chehab, Zaki" (London, 2006)
Provides a picture of the Iraqi insurgency in all its complexity, ferocity and passion. The author shows how the resistance fighters really view the post-saddam regime, George W Bush and the terrorist phenomenon now known as 'al-Qaeda'. He also reveals facets of the occupiers' Strategy.
Keywords: War-Iraq